2014
DOI: 10.3389/fnbeh.2014.00121
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide S and BDNF gene expression in the amygdala are influenced by social decision-making under stress

Abstract: In a newly developed conceptual model of stressful social decision-making, the Stress-Alternatives Model (SAM; used for the 1st time in mice) elicits two types of response: escape or remain submissively. Daily (4d) aggressive social interaction in a neutral arena between a C57BL6/N test mouse and a larger, novel aggressive CD1 mouse, begin after an audible tone (conditioned stimulus; CS). Although escape holes (only large enough for smaller test animals) are available, and the aggressor is unremittingly antago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(71 citation statements)
references
References 80 publications
(122 reference statements)
4
67
0
Order By: Relevance
“…Synaptic plasticity is promoted by bdnf, as are neurogenesis, cell survival and the strengthening of learning and memory (Mattson et al, 2004). Recently, Smith et al (2014) characterised forebrain bdnf expression in mice that displayed differential behavioural responses to social aggression and fear conditioning. They reported that mice that chose to escape an aggressive conspecific showed higher bdnf abundance in the amygdala compared with individuals that did not escape.…”
Section: Discussionmentioning
confidence: 99%
“…Synaptic plasticity is promoted by bdnf, as are neurogenesis, cell survival and the strengthening of learning and memory (Mattson et al, 2004). Recently, Smith et al (2014) characterised forebrain bdnf expression in mice that displayed differential behavioural responses to social aggression and fear conditioning. They reported that mice that chose to escape an aggressive conspecific showed higher bdnf abundance in the amygdala compared with individuals that did not escape.…”
Section: Discussionmentioning
confidence: 99%
“…The sequences of probe and primer sets are listed in Table 1 and were derived from sequences produced by McFarlan et al (2009) for another passerine bird species, the white-throated sparrow (Zonotrichia albicollis). We quantified changes in mRNA expression using the 2 −ΔΔCT method (Livak and Schmittgen 2001;Smith et al 2014) comparing all samples to a reference sample. We normalized mRNA expression for lipid transporters to GAPDH mRNA expression in the same sample to determine relative amounts of mRNA expression.…”
Section: Mrna Expressionmentioning
confidence: 99%
“…The Stress-Alternatives Model (SAM) assesses anxious and depressive behaviors plus influences on decision-making (Smith et al, 2014), parsing active responses into contextual niches along an anxiety gradient. In the open field test (OF) rodents avoid the open center, which is reversed by anxiolytic drugs (Heredia et al, 2014).…”
Section: Introductionmentioning
confidence: 99%